2021
DOI: 10.5430/rwe.v12n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and Crisis in Greece From a neo-Schumpeterian Perspective: A Suggestion to Stimulate the Development Process at the Local Level

Abstract: In economies where most firms are family-owned, there is a risk of poor management and problematic strategic and technological comprehension. Multiple cases prove the existence of a series of socio-economic pathologies in such firms that undermine an economy’s ability to overcome economic crises through innovative and entrepreneurial thinking and adaptability. The paper aims to present the relationship between entrepreneurship and “development and crisis” from the perspective of Greece’s current socio-economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…On the other hand, Vlados et al (2021) suggested that in economies where most firms are family-owned, there is a risk of poor management and problematic strategic and technological comprehension, which may undermine an economy's ability to overcome economic crises through innovative and entrepreneurial thinking and adaptability. Soluk et al (2021) found that an exogenous shock (such as COVID-19) further reinforces the family firms' resource constraints and the family's fear of losing their socioemotional wealth.…”
Section: Family Ownershipmentioning
confidence: 99%
“…On the other hand, Vlados et al (2021) suggested that in economies where most firms are family-owned, there is a risk of poor management and problematic strategic and technological comprehension, which may undermine an economy's ability to overcome economic crises through innovative and entrepreneurial thinking and adaptability. Soluk et al (2021) found that an exogenous shock (such as COVID-19) further reinforces the family firms' resource constraints and the family's fear of losing their socioemotional wealth.…”
Section: Family Ownershipmentioning
confidence: 99%
“…In more developed economies, the tertiary sector focuses increasingly on offering intermediate services (business-to-business), bringing significant advantages to other sectors of economic activities (Mora Cortez and Johnston, 2018). This evidence reaffirms that the Greek crisis is structural and due to the relatively weak competitiveness of most Greek firms (Vlados et al, 2021).…”
Section: 2mentioning
confidence: 67%
“…Therefore, these findings seem to confirm that most sample MFs are “monad-centered” (revolve around the owner’s persona, the “monad”) in terms of organizational physiology Stra.Tech.Man. According to the relevant typology of Vlados et al (2021), the three forms of entrepreneurship in Greece are “monad-centeredness,” “massiveness” and “flexibility.” The vast majority of firms seem adjacent to “monad-centered” physiology. This fact appears to create competitiveness problems in the Greek economy as these organizations follow instinctive forms of strategy, sporadic technological choices and management methodologies exhausted in the daily market experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while both regions are home to innovative businesses [42], there is a great deal of room for growth, as well as for a reorientation of the regional economies towards more innovative sectors and practices. The start-up ecosystem in Greece can play a key role as a driver of further innovation by making use of the available intellectual capital [43], but the nascent innovative start-up scene is facing many obstacles. Apart from the lack of entrepreneurial skills and training [44], these include underdeveloped collaborative networks, low R&D investments, an unfriendly business environment afflicted by bureaucracy, and obsolete, punitive business legislation, which creates a constant fear of bankruptcy [45][46][47].…”
Section: Figurementioning
confidence: 99%